Operationalizing seasonal work in Germany - Jochen Späth; Tobias Brändle; Stefan Preuss; Marcel Reiner (Institut für Angewandte Wirtschaftsforschung (IAW), 2018)
Due to a lack of sector-overarching, frequent and representative data, only little is known about the prevalence of seasonal workers in the German labor market and, in particular, about their working conditions such as forms of employment, working hours or even wages. We estimate seasonal work in Germany using a custom, representative sample of the Employment History (BeH) of the Federal Employment Agency (BA) that encompasses information on short-term employees that are new to scientific research. We achieve a reasonable fit to the - less frequent and sectorally restricted - Farm Structure Survey by the German Federal Statistical Office suggesting our method for future analyses of seasonal work. Our analyses reveal large differences between economic sectors, the share of seasonal work being highest in agriculture and forestry, followed by hotels and restaurants. While in agriculture and forestry the vast majority of seasonal workers is given by short-term employment, in the hotel and restaurant industry marginally paid (part-time) employment is the dominant type. Since 2012, the number of seasonal workers has increased in all investigated economic sectors. That said, there are hardly any signs of significant spikes since the introduction of the general minimum wage in 2015.
Keywords: J21; J61; J43; 330; Seasonal Work; agriculture and forestry; gardening and landscaping; hotels and restaurants; Beschäftigtenhistorik